Africa's Development: Institutions, Economic Reforms and Growth - Amin, Aloysius Ajab (International Journal of Economics and Financial Issues, 2013)
The paper examines the importance of relative prices, institutional quality and other factors which are regressed on the estimated total factor productivity (TFP). With panel data of 26 African countries for the period 1980-2011, the results show that relative prices have significant effects on TFP. Also the quality of institutions is an important determinant of non-input component of output growth. The macroeconomic measures to get “prices right” in sub Saharan Africa may also be constrained by the linkages of institutions to the macroeconomic variables. Thus, policies of getting prices right with establishing strong institutions are worth continuously pursuing with vigor. Keywords: Prices; Growth; Total-factor-productivity; Africa; Institutions JEL Classifications: P22: O43; O55; O47